2020
DOI: 10.3847/1538-4365/ab6dce
|View full text |Cite
|
Sign up to set email alerts
|

Cross Helicity Reversals in Magnetic Switchbacks

Abstract: We consider 2D joint distributions of normalised residual energy σ r (s, t) and cross helicity σ c (s, t) during one day of Parker Solar Probe's (PSP's) first encounter as a function of wavelet scale s. The broad features of the distributions are similar to previous observations made by HELIOS in slow solar wind, namely well correlated and fairly Alfvénic, except for a population with negative cross helicity which is seen at shorter wavelet scales. We show that this population is due to the presence of magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…respectively, marked as solid black lines. In general, it can be seen that in both cases the fluctuations are highly Alfvénic (σ c ≈ 1, σ r ≈ 0, r E 1, r A ≈ 1), more so than in previous encounters (Chen et al 2020;McManus et al 2020;Parashar et al 2020), but the near-HCS wind is less Alfvénic than the wind far from the HCS. The averages for these different regions are given in Table 1.…”
Section: Hcs Proximity Dependencementioning
confidence: 66%
“…respectively, marked as solid black lines. In general, it can be seen that in both cases the fluctuations are highly Alfvénic (σ c ≈ 1, σ r ≈ 0, r E 1, r A ≈ 1), more so than in previous encounters (Chen et al 2020;McManus et al 2020;Parashar et al 2020), but the near-HCS wind is less Alfvénic than the wind far from the HCS. The averages for these different regions are given in Table 1.…”
Section: Hcs Proximity Dependencementioning
confidence: 66%
“…D' Amicis et al (2019) reported that the slow solar wind with high Alfvénicity share common characteristics with the fast wind, and Perrone et al (2020) further observed that Alfvénic slow wind shows a break between the inertial range and large scales where the magnetic fluctuations saturate. It seems plausible that this −1 frequency range is related to the observations of Alfvénic switchbacks (de Wit et al 2020;Horbury et al 2020;Mozer et al 2020;McManus et al 2020), close the Sun, that provide most of the energy-containing range in the slow wind. Later on other processes such as stream interactions and reconnection could furnish the large scales and the cascade (even at lower rates).…”
Section: Discussionmentioning
confidence: 83%
“…However we feel that the above method of fitting to both the contaminant protons and alpha particles at the same time, using fitted parameters from the SF00 channel, better accounts for overlap between the proton and alpha distributions, especially in slow solar wind. This is also important during the ubiquitous magnetic field reversals or switchbacks observed so far by PSP (de Wit et al 2020;McManus et al 2020), because the associated speed enhancements in the protons causes greater overlap of the proton and alpha VDFs in velocity space. Finally, spacecraft motion is removed from the fitted proton and alpha parameters to obtain plasma velocities in RTN coordinates.…”
Section: Alpha Channel Contaminationmentioning
confidence: 95%